IL18 Polymorphism and Periodontitis Susceptibility, Regardless of IL12B, MMP9, and Smoking Habits - Patrícia Yumeko Tsuneto; Victor Hugo de Souza; Josiane Bazzo de Alencar; Joana Maira Valentini Zacarias; Cléverson O. Silva; Jeane Eliete Laguila Visentainer; Ana Maria Sell (Mediators of Inflammation)
Genetic variations contribute to the susceptibility in the development of periodontitis. The aim of this study was to investigate the influence of IL18, IL12, and MMP9 polymorphisms in the chronic periodontitis. This case-control study involved 381 individuals matched by gender and age. Genotyping of IL18 (rs187238 and rs1946518) and IL12B (rs3212227) was performed by PCR-SSP and PCR-RFLP was used for MMP9 (rs3918242). IL-18 and MMP-9 were quantified in the serum by ELISA. SNPStats and OpenEpi software were used for statistical analysis and, in order to eliminate smoking as a confounding factor, the analyses were also performed in nonsmoking subjects. The IL18-137G/C genotype was associated with the risk of chronic periodontitis in nonsmokers (Pc=0.03; OR=1.99; overdominant inherence model). In the multivariate analyses, homozygous IL18-137G/G and IL18-607C/C were more frequent in males compared to women with these same genotypes (OR=2.51 and OR=3.30, respectively). The serum levels of the IL-18 in patients were higher than those in healthy controls (P=0.005). IL12B and MMP9 polymorphisms and MMP-9 serum concentration were similar in patients and controls. In this study, IL18 was associated with chronic periodontitis susceptibility. Men had greater risk than women for developing the disease when IL18 polymorphism was considered and the susceptibility was independent of the smoking status.